6.8k views
0 votes
Help me pleasee!!




thank you

Help me pleasee!! thank you-example-1

1 Answer

3 votes

Explanation:

so, we need to get the slope-intercept form

f(x) = y = ax + b

"a" is as always the slope, "b" is the y-intercept (the y-value when x = 0).

as we have the slope and a point, we can start with the point-slope form and transform it :

y - y1 = a(x - x1)

with (x1, y1) being a point on the line.

y - 7 = -9(x - 2) = -9x + 18

y = -9x + 25

therefore, the functional equation is

f(x) = -9x + 25

User Izabella
by
4.7k points